HUBUNGAN MOTIVASI BELAJAR DAN GAYA BELAJAR VARK DENGAN PRESTASI AKADEMIK MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS ISLAM AL-AZHAR - Syilvia Saswati; Dina Qurratu Ainin; Ronanarasafa; Dian Rahadianti (Yayasan Nusantara Hasana Berdikari, 2023)
Medical education is an educational process that is not easy and learning medicine is a long life learning. So it is important to have high motivation and the right learning style in order to complete medical education with satisfactory results. This study aims to determine the relationship between learning motivation and VARK learning style with academic achievement. This study used a quantitative analytic observational research design with a cross sectional study design. The sampling technique used proportionate stratified random sampling technique and obtained a sample of 81 respondents. The data obtained were analyzed with the Chi-Square correlation test. The significance value limit is (P-value <0.05). Most of the students' academic achievements were in the very good category (GPA 3.00-4.00) for 53 students (65.4%). Most of the students had a high motivation of 51 students (63.0%) and a kinesthetic learning style of 63 students (77.8%). The results of the bivariate analysis test of learning motivation and learning achievement obtained a p-value of 0.000 (p <0.05) meaning that there is a significant relationship. The results of the VARK learning style bivariate analysis test with learning achievement obtained a p-value of 0.694 (p>0.05) meaning that there was no significant relationship. There is a relationship between learning motivation and academic achievement of Al-Azhar Islamic University Medical Faculty students. However, there is no relationship between VARK learning style and academic achievement of Al-Azhar Islamic University Medical Faculty students.